A new T helper 17 cytokine in hidradenitis suppurativa: antimicrobial and proinflammatory role of interleukin‐26. (23rd June 2019) - Scala, E.; Di Caprio, R.; Cacciapuoti, S.; Caiazzo, G.; Fusco, A.; Tortorella, E.; Fabbrocini, G.; Balato, A.
Summary: Background: Interleukin (IL)‐26 is a signature T helper 17 cytokine described as a proinflammatory and antimicrobial mediator. So far, IL‐26 has been reported in several immune‐mediated inflammatory diseases, but its involvement in inflammatory skin disorders is poorly known. Objectives: To investigate the role of IL‐26 in hidradenitis suppurativa (HS), through its involvement in antimicrobial activity. Methods: IL‐26 was assessed in patients with HS through gene expression and protein analysis at skin and circulating levels. Ex vivo HS organ skin cultures, together with IL‐26 antibody treatment, were performed to determine the IL‐26 activity. Peripheral blood mononuclear cells (PBMCs) from patients with HS and healthy controls were either silenced or not with IL‐26 small interfering (si)RNA in order to measure its antimicrobial, cytotoxic and phagocytic activities against Staphylococcus aureus . Results: Firstly, we observed that IL‐26 is able to modulate the proinflammatory response at the immune cell level. IL‐26 was increased in the plasma of patients with HS compared with healthy controls. Subsequently, we explored the bactericidal, cytotoxic and phagocytic activities of PBMCs against S. aureus in patients with HS and healthy controls. These activities were lower in patients with HS than in controls. Remarkably, the killing activities were reduced when healthy control PBMCs were transfected with IL‐26 siRNA. However, the transfection did not affect the killing activity of HS PBMCs, supporting the idea that IL‐26 lacks efficacy in HS. Conclusions: Our findings suggest that infection susceptibility in HS might be related to IL‐26. Although the role of bacteria remains controversial in HS, this paper supports that there is a defect of antimicrobial response in these patients. What's already known about this topic? Interleukin (IL)‐26 is a T helper 17 cytokine described as an antimicrobial and proinflammatory mediator. IL‐26 has been reported in immune‐mediated inflammatory diseases, but its involvement in inflammatory skin disorders remains unclear. Hidradenitis suppurativa (HS) is a chronic inflammatory skin disorder characterized by deficiency of IL‐20 and IL‐22 (a close homologue of IL‐26), which causes antimicrobial peptide pauperization leading to severe and recurrent skin infections. What does this study add? IL‐26 plasma levels are higher in patients with HS than in healthy control individuals. The antimicrobial activity of IL‐26 might be ineffective in patients with HS. What is the translational message? Cutaneous antimicrobial incompetence in HS could be related to IL‐26. Abstract : Linked Comment: Giamarellos-Bourboulis. Br J Dermatol 2019; 181 :892–893 . Respond to this article